Violences conjugales en période de crise sanitaire : les politiques publiques britanniques à l’épreuve de « la pandémie fantôme » - Corinne Nativel (Revue Française de Civilisation Britannique)
On 23 March 2020, Boris Johnson’s government declared a lockdown in response to the Covid-19 pandemic that was spreading across the country. Very quickly, feminist domestic violence associations alerted the public authorities to the emergence of a “shadow pandemic”. By being locked up in the marital home, women victims were overexposed to the risks of violence. Statistical data and various quantitative and qualitative surveys produced by different agencies and scientific research have largely corroborated this warning. This article examines the responses provided by the public authorities at national level and by local actors. It shows that the pandemic crisis acted as a magnifying mirror and provoked emergency responses aimed at managing the immediate risk without producing a real paradigm shift or a reconfiguration of public policies. In this sense, it may be an epiphenomenon rather than a real turning point in the history of the fight against Violence against women and girls in the UK.